Chest Soft Tissue Schwannoma: a Difficult Case of Diagnosis - M. V. Perevedentsev; E. A. Podolskaya; N. S. Vorotyntseva; E. N. Kretova (Вестник рентгенологии и радиологии)
The article presents a clinical case of a patient born in 1963, examined and treated at Ostroverkhov Kursk Oncology Scientific and Clinical Center in 2024. The complexity of schwannoma preoperative diagnosis was illustrated: a complete discrepancy between complaints and clinical manifestations, rare localization for schwannoma (chest wall soft tissues, retroperitoneal space), discrepancies in the results of comprehensive preoperative diagnosis (multislice computed tomography, ultrasound, positron emission tomography with computed tomography), problems of histological examination of biopsy material obtained during tumor core biopsy under ultrasound control. The final diagnosis was established only after performing a radical operation with rib resection. The publication can help radiologists, ultrasound diagnosticians, morphologists, oncologists, surgeons to accumulate clinical experience for choosing optimal diagnostic methods and developing an algorithm for patient management.